Using measured resting metabolic rate to derive calorie prescriptions in a behavioral weight loss program - Autumn Lanoye; Ronald K. Evans; Tricia M. Leahey; Jessica G. LaRose (Obesity Science & Practice, 2021)
Abstract Objective Within behavioral weight loss (BWL) programs, using measured resting metabolic rate (RMR) is a more accurate—yet costlier—alternative to the standard method of assigning calorie prescriptions using baseline weight. This investigation aimed to assess differences between calorie goals prescribed using each method including demographic predictors and associations with weight loss. Methods This is an ancillary study to a trial comparing approaches to motivational enhancement in a 6‐months BWL program designed for emerging adults age 18–25 (N = 308). RMR was measured at baseline and used to derive calorie prescriptions; standard calorie goals were retrospectively assigned for the purpose of these analyses. Results Standard calorie prescriptions were significantly higher than those derived from RMR. Sex and race were significant predictors of calorie prescription discrepancies: using the standard method, women and Black participants were assigned higher calorie goals than their RMR would indicate. Calorie goal discrepancy did not predict 6‐months weight change. Conclusions Differences in calorie prescriptions between approaches were significant; however, it remains to be determined whether measuring RMR is worth the cost, time, and participant burden. It may be the case that this consideration has greater impact for certain subgroups—namely, women and Black participants.